2010
DOI: 10.1128/jvi.00496-10
|View full text |Cite
|
Sign up to set email alerts
|

Delaying the Expression of Herpes Simplex Virus Type 1 Glycoprotein B (gB) to a True Late Gene Alters Neurovirulence and Inhibits the gB-CD8 + T-Cell Response in the Trigeminal Ganglion

Abstract: Following herpes simplex virus type 1 (HSV-1) ocular infection of C57BL/6 mice, activated CD8؉ T cells specific for an immunodominant epitope on HSV-1 glycoprotein B (gB-CD8 cells) establish a stable memory population in HSV-1 latently infected trigeminal ganglia (TG), whereas non-HSV-specific CD8 ؉ T cells are lost over time. The retention and activation of gB-CD8 cells appear to be influenced by persistent viral antigenic exposure within the latently infected TG. We hypothesized that the low-level expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 33 publications
1
36
0
Order By: Relevance
“…(ii) gB1 induces strong humoral and cell-mediated immune responses (17,35). (iii) It contains "protective" cytotoxic-T-lymphocyte (CTL) epitopes that are preferentially recognized by asymptomatic subjects, are important to prevent recurrent diseases, and maintain HSV-1 in a latent state (12,45). (iv) Finally, gB1 is highly conserved within and between HSV-1 and HSV-2 serotypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(ii) gB1 induces strong humoral and cell-mediated immune responses (17,35). (iii) It contains "protective" cytotoxic-T-lymphocyte (CTL) epitopes that are preferentially recognized by asymptomatic subjects, are important to prevent recurrent diseases, and maintain HSV-1 in a latent state (12,45). (iv) Finally, gB1 is highly conserved within and between HSV-1 and HSV-2 serotypes.…”
Section: Discussionmentioning
confidence: 99%
“…The strategies tested included genetically attenuated live virus, whole inactivated virion preparations, recombinant subunit vaccines, gene-delivery vehicles expressing structural or nonstructural HSV antigens, and DNA plasmid expressing HSV antigens (reviewed in references 17 and 38). Most of these approaches failed during animal study or in early phases of human trials, but a few have received the more consideration since they were able to reduce the rate of acquiring HSV-2 genital infection in HSV-seronegative women (45). These results offered hope that vaccination against HSV-2 is possible but also showed that improvement of current and development of novel concepts were clearly necessary (17).…”
mentioning
confidence: 99%
“…The more striking feature in the present study was that the phosphorylation, as well as the enzymatic activity, of vdUTPase played no role in viral replication and pathogenicity in the eyes and vaginas of mice following ocular and vaginal inoculation, respectively. To our knowledge, HSV proteins or their domains critical for viral replication and virulence in the CNS of mice following intracranial inoculation are, in almost all cases, also involved in pathogenicity in peripheral sites, such as eyes and vaginas, following peripheral (ocular and vaginal) inoculation (7,10,11,15,27,41,(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59). Therefore, this phosphorylation reaction, which promoted the vdUTPase activity, is a unique indication of a specific mechanism involved in HSV-1 replication and virulence in and replication in mice.…”
Section: Fig 5 Effect Of Mutations In Vdutpase or The Kinase-dead Mutmentioning
confidence: 99%
“…The regulation of T cell responses during persistent infections may vary depending on several factors, including the quality of T cell priming, the anatomical sites of viral persistence, the inflammatory microenvironment, and the timing and duration of cognate antigen presentation (29-34). It is unclear how the antiviral T cell response is maintained long-term during persistent γ-herpesvirus infections.…”
Section: Discussionmentioning
confidence: 99%